Eyelid Retraction in Isolated Unilateral Congenital Blepharoptosis - Salman, Michael S.; Clark, Ian H. (Frontiers in Neurology, 2017)
Isolated unilateral congenital ptosis is encountered relatively infrequently in clinical practice. It typically consists of a unilateral droopy eyelid, weak levator palpebrae superioris muscle function, lid lag, and an absent upper lid crease with no other abnormalities on examination. We present a four-and-a-half year old girl with isolated and mild unilateral congenital ptosis who unexpectedly demonstrated a static upper eyelid on downgaze in conjunction with a well-formed upper lid skin crease. We attribute this uncommon sign in congenital ptosis to stiffness and presumed fibrosis of the levator muscle. Examining the function of the eyelids in all directions of gaze is important in patients with abnormalities of lid position, since additional useful information can be gleaned about the status of the levator muscle including, aberrant regeneration or fibrosis.